Ergonomia pracy przy komputerze – spojrzenie okulisty - Mrugacz, Małgorzata; Szumiński, Michał (Klinika Oczna / Acta Ophthalmologica Polonica, 2009)
Ergonomics in computerized workplace contributes to create special environmental conditions depending on people’s needs and possibilities. Ergonomically created room with accurate type of lighting, temperature and humidity, furniture and location of PC unit and monitor is essential to avoid symptoms of computer stress syndrome.